Participatory demonstration and evaluation of improved onion variety in East Shewa zone of Oromia regional state, Ethiopia - Miruts, Fistum; Roba, Belay; Sori, Derara (Agriculture and Food Sciences Research, 2023)
The study was carried out in selected districts of East Shewa zone Oromia regional state to compare the performance of a recently released onion variety (Nafis) with their recommended agronomic recommendations to a control (Bombay red) through an on-farm demonstration. The demonstration was implemented on 9.3 hectares of 37 farmers’ farmland. The Nafis variety outperformed the control, with a mean yield of 293.2 qt/ha. The mean technology gap was 106.8 qt/ha and the technology index recorded was observed to be 26.7%. Farmers’ preferences were used to evaluate onion varieties with criteria of yield, disease, bulb size, bulb color (deep red preferred), pungency, storability, and market preference. Nafis variety is preferred over the Bombay red variety. In addition, lack of improved seeds, high chemical costs, and insect and disease infestations are among the major constraints limiting onion production and productivity in the study area. Trips and fungi (Purple Bloch) have also been identified by farmers as a major disease affecting onion production in the districts. In general, the demonstrated variety (Nafis) was found to be feasible and preferred by the farmers to cultivate in the East Shewa zone as compared to the check (Bombay red). Therefore, onion yield in farmers’ fields can be improved largely by cultivating the Nafis variety in the study area and similar environments.